Identification of triterpenes and sterols from Pterogyne nitens (fabaceae-caesalpinioideae) using high-resolution gas chromatography - Regasini, Luis Octávio [UNESP]; Vieira-Júnior, Gerardo Magela [UNESP]; Fernandes, Daniara Cristina [UNESP]; Bolzani, Vanderlan Da Silva [UNESP]; Cavalheiro, Alberto José [UNESP]; Silva, Dulce Helena Siqueira [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2009)
As part of our ongoing bioprospecting studies on secondary metabolites in plants of Cerrado and Atlantic Rain Forest of São Paulo State (Brazil), we describe the identification of triterpenes and sterols present in the hexane extracts and foliar epicuticular wax of Pterogyne nitens Tulasne (Fabaceae-Caesalpinioideae) using high resolution gas chromatography. Compounds detected in these extracts include β-amyrin (1), taraxerol acetate (2), lupenone (3), β-amyrenone (4), germanicone (5), campesterol (6), stigmasterol (7), and β-sitosterol (8). The method reported herein is shown to be a rapid, sensitive and reproducible tool for describing triterpenes and sterols present in non-polar extracts.
Keywords: Fabaceae-Caesalpinioideae; Gas chromatography; Pterogyne nitens; Sterols; Triterpenes